ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MA MENGGUNAKAN PENDEKATAN PROBLEM BASED LEARNING - Sudirman Sudirman; Luvy Sylviana Zanthy (Journal on Education, 2019)
Problem solving ability is an important mathematical ability for students to solve existing problems. This study aims to analyze students' mathematical problem solving abilities in the story problems of three-variable linear equation systems. This research was conducted in class X in one of the Alliyah Madrasas in Cianjur. The approach used is a problem based learning approach with a qualitative descriptive method. The instrument consists of 6 pieces of problem solving story problems. The test done by students is given a score and in the analysis of errors in answering the questions. The results of the study show that of the 40 class X students only 4 students can complete the conclusion, 13 students complete the process skills, 24 students complete the transformation phase and 32 students can complete the problem understanding stage. In terms of problem solving abilities in class X in one of the Alliyah Madrasas in Cianjur is still weak.